Analysis Of The Effect Of Management Control On Organization Performance and Innovative Behavior - Amelia Safana Syafiqah; Muhammad Rafi Khalid; Adrian A. Wijanarko (SEAN Institute, 2024)
The purpose of this study will focus on how the influence of Management Control on Innovative Behavior and Organization Performance in various companies, both on a regional, national and international scale. The method used in this study is a quantitative method, where data is obtained through the distribution of questionnaires in the form of Google Form developed based on predetermined constructs to respondents who have a minimum position of supervisor and have subordinates, with each Management Control question totaling 12 questions, Innovative Behavior totaling 8 questions, and Organization Performance has 3 questions. Respondent collection using non-probability sample and convenience sampling. The number of respondents who answered was 101 people. The collected data will be analyzed using statistical techniques to test the research hypothesis. The calculation was done using the Statistical Package for the Social Sciences (SPSS) tool. The results showed that Management Control positively affects Innovative Behavior and Organization Performance, and Innovative Behavior positively affects Organization Performance